Effect of the paclitaxel vehicle, Cremophor EL, on the pharmacokinetics of doxorubicin and doxorubicinol in mice. - Webster, L. K. (Nature Publishing Group, 1996)
The effect of the paclitaxel vehicle Cremophor on the pharmacokinetics of doxorubicin and doxorubicinol was studied in two groups of mice given intravenously either 2.5 ml kg-1 Cremophor or saline followed 5 min later by 10 mg kg-1 doxorubicin. In each group three mice were sacrificed at ten time points and doxorubicin and doxorubicinol were measured in plasma by high-performance liquid chromatography (HPLC). With Cremophor present, doxorubicin AUC increased from 1420+/-440 to 2770+/-660 ng h ml(-1) (P<0.05) and doxorubicinol AUC increased from 130+/-76 to 320+/-88 ng h ml(-1) (p<0.05). Neither the terminal elimination half-lives nor the doxorubicinol-doxorubicin AUC ratio changed in the presence of Cremophor, suggesting a lack of a direct effect on drug metabolism. The possibility exists the Cremophor may change the pharmacokinetics of both paclitaxel and other drugs given concurrently.